Solifenacin – first experiences in overactive bladder treatment - Surkont, Grzegorz; Wlaźlak, Edyta; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2006)
Aim of the study: In the article we presented first our experiences with ovaractive bladder (OAB) treatment with the use of new antimuscarinic drug Vesicare (Astellas). Material and methods: In the analysis we included first 20 patients aged 57-81 with OAB complaints. We analised first two months of treatment with solifenacin used in oral tablets in dose 5 mg given once daily. Patients were evaluted before and after 8 weeks of treatment. In the study we evaluated the efficacy of treatment and patient’s compliance. Conclusions: Solifenacin in 5 mg dose is efficient in OAB treatment. It is well tolerated. Side effects on low level are rare. These conclusions are preliminary. More detailed analysis will be possible after long-time evaluations on bigger numbers of patients.